2020
DOI: 10.1186/s12936-020-03296-4
|View full text |Cite
|
Sign up to set email alerts
|

Submicroscopic malaria infection is not associated with fever in cross-sectional studies in Malawi

Abstract: Background: Submicroscopic Plasmodium falciparum infections are widespread in many areas. However, the contribution of these infections to symptomatic malaria is not well understood. This study evaluated whether participants with submicroscopic P. falciparum infections have higher prevalence of fever than uninfected participants in southern Malawi. Methods: A total of 16,650 children and adults were enrolled in the course of six cross-sectional surveys during the dry season (October-November) and after the rai… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…In high transmission areas in sub-Saharan Africa, there are conflicting reports on the clinical relevance of submicroscopic infections. A cross-sectional survey in Malawi found no association between submicroscopic infection and clinical manifestation of malaria [ 54 ] whereas a recent study in Bagamoyo, Tanzania, was inconclusive on the contribution of submicroscopic infections to malaria transmission [ 55 ]. Meanwhile, longitudinal studies in Uganda found significant association between submicroscopic infections and febrile/non-febrile illnesses in younger children but not in adults [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…In high transmission areas in sub-Saharan Africa, there are conflicting reports on the clinical relevance of submicroscopic infections. A cross-sectional survey in Malawi found no association between submicroscopic infection and clinical manifestation of malaria [ 54 ] whereas a recent study in Bagamoyo, Tanzania, was inconclusive on the contribution of submicroscopic infections to malaria transmission [ 55 ]. Meanwhile, longitudinal studies in Uganda found significant association between submicroscopic infections and febrile/non-febrile illnesses in younger children but not in adults [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…36 Explanations for these heterogenous thresholds are uncertain, but may relate to undetected current or recent inflammatory disease. For example, asymptomatic submicroscopic Plasmodium parasitaemia is highly prevalent in sub-Saharan African children, 65,66 while in India the incidence of acute respiratory infections in children under 3 years is 2766 per 1000 child years, 67 and about 22% of Bangladeshi infants receive some form of health care due to illness (usually fever, vomiting or diarrhoea) over a three month period. 68 We found evidence for heterogeneity of both common and rare genetic effects on haemoglobin across different ancestries, including two variants proximal to the alpha-thalassaemia genes (HBA1/ HBA2) which show larger effect sizes than might be expected given their frequency within individuals of African ancestry.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of infections detected in community-based surveillance are submicroscopic, and these low-density infections are not associated with fever. 8 However, a small proportion of infections causes clinical disease. Through a longitudinal cohort of adults and children at a rural health center, we demonstrated that asymptomatic parasitemia was present in 23% of all visits.…”
Section: Epidemiology Of P Falciparum Infection An...mentioning
confidence: 99%